Identification and Mitigation of Pameling Avocado Supply Chain Risk Using The Fuzzy Analytical Hierarchy Process (F-AHP) Method - Naafila, Ludzna Yus'ida; Isaskar, Riyanti; Dewi, Heptari Elita; Assawwa, Laily Yuthiika (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2023)
Risk is related to uncertainty that has the potential to occur and can have a negative impact on the company if not handled. Risks in the product supply chain have a greater impact on agricultural products. The purpose of this research is to analyze the pameling avocado supply chain system at PT. S, knowing supply chain risk priorities based on fuzzy AHP calculations, and determining pameling avocado supply chain risk mitigation at PT. S for each actor. Respondents were taken by purposive sampling consisting of 3 farmers, 3 middleman, 1 person from the company, namely the marketing general manager, and 1 retailer representative. Pameling avocado supply chain system at PT. S has 2 types of marketing channels, so that supply chain actors consist of 4 actors, namely farmers, middlemen, companies (PT. S), and retailers. Based on the Fuzzy AHP calculation, the priority risk at the farm level is environmental risk, with priority risk indicators being that land conditions do not support growth requirements (too dense soil, lack of nutrients). At the middleman level, the priority risk is price risk, with the priority indicator being the amount of marketing/distribution costs. At the company level, the highest risk priority is quality risk, with product damage priority risk indicators. Then, At the retailers, the highest risk priority is supply risk, with priority risk indicators in the form of uncertainty in the quantity of pameling avocado stock. Risk mitigation is designed using a descriptive analysis method with interview techniques and literature studies.